Living on High Altitudes Associated with Reduced Requirements of Exogenous Erythropoietin in Patients on Chronic Hemodialysis - André Benítez; David Garrido; Andrea Banegas; María Belén Mena; Washington Osorio; Jorge Rico-Fontalvo; Maria Raad-Sarabia; Rodrigo Daza-Arnedo; Maria Cardona-Blanco; Tomas Rodriguez-Yanez; Liseth Sierra-Torres (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2024)
Introduction: During the last decades the use of erythropoiesis stimulating agents has significantly diminished the prevalence of anemia in patients receiving chronic hemodialysis. Currently, residing at higher altitudes is associated with higher levels of endogenous erythropoietin. Objective: This study aims to analyze how residing at higher altitudes influences the requirements of exogenous erythropoietin in patients receiving hemodialysis as renal replacement therapy. Methodology: Descriptive observational cross-section, including adult patients from three Ecuadorian centers, receiving chronic hemodialysis, between January and June 2020. Patients were classified into two groups regarding the altitude of residence: those living at low-lying regions (<2000 masl, Santo Domingo de los Tsachilas and Tena) and those living at high altitude (>2000 masl, Quito). Results: We included 580 patients, 45.5% in the high-altitude group and 54.5% at low-lying regions. Median exogenous erythropoietin dose was higher in low-lying regions (22000 international units) versus high altitude (17333.3 international units) (P=0.00003) and the proportion of patients without erythropoietin requirement was higher in high altitude (21.6%), compared to low regions (1.0%) (P<0.01). The multivariate analysis associated residing in low regions (HR 58.9, P<0.01), age (HR 0.98, P=0.03) and Kt/V (HR 38.5, P<0.01) with higher exogenous erythropoietin requirements. Additionally, among patients who required erythropoietin, residing in lower altitudes was linked with a need for exogenous erythropoietin doses exceeding 15000 international units per week (HR 1.92, P=0.001). Conclusion: In Ecuadorian patients receiving hemodialysis, living at high altitude is associated with a reduced requirement of exogenous erythropoietin compared with those patients residing in low-lying regions.